An encryption approach for product assembly models. (August 2017) - Cai, X.T.; Wang, S.; Lu, X.; Li, W.D.
Abstract: In a collaboration environment, it is a challenge how to effectively share the information needed for collaboration while protecting other confidential information in a product assembly model. In this paper, an innovative encryption approach for assembly models to support collaboration is presented. This approach is content based encryption and effective for the secure sharing of feature-based assembly models. In the approach, a classification algorithm for features in an assembly model to be shared or protected during collaboration has been first developed. An encryption algorithm for a feature has been then designed to ensure the parameterization, topological and geometrical validity, and self-adaptability of the encrypted feature. An algorithm for parts with multiple encryption features has been developed. Based on the above algorithms, parts are finally assembled and the geometry and topology of the assembling structure are kept un-changed to enhance collaborators' interoperability. The characteristics and innovations of the approach include: (1) the approach is feature based, integrative into the main-stream commercial Computer Aided Design (CAD) systems, and flexible to meet various users' needs for encrypting features selected by users during collaboration, (2) in the approach, the topological and geometrical validity of an assembly model after encryption is maintained to ensure effective collaboration on the assembly, and (3) the approach is parametrically controlled through adjusting position and size parameters so as to ensure the user friendliness of using the approach. A case study with complex geometries and assembly structures has been used to validate the effectiveness and robustness of the approach in industrial applications.